Weighted Neutrosophic Soft Sets - Pabitra Kumar Maji (Neutrosophic Sets and Systems, 2014)
In this paper we study the concept of neutrosophic soft sets. Imposing some weights on the parameters considered we introduce here weighted neutrosophic soft sets. Some operations like union, intersection, complement, AND, OR etc. have been defined on this new concept. Some properties of these newly defined operations have also been verified.